Comparison between patching and interactive binocular treatment in amblyopia: A randomized clinical trial - Rajavi, Zhale; Sabbaghi, Hamideh; Amini Sharifi, Ebrahim; Behradfar, Narges; Kheiri, Bahareh (Iranian journal of ophthalmology, 2019)
To compare the effect of amblyopia therapy on cases who received interactive binocular treatment (I-BiT™) with those who received standard patching of the dominant eye with placebo I-BiT™. In this randomized clinical trial, 38 unilateral amblyopic children (3–10 years old) were studied. All unilateral amblyopic children who had best corrected visual acuity (BCVA) worse than 0.30 logMAR or a difference of two Snellen lines of BCVA between their two eyes were included, and children who did not complete at least 75% of amblyopia treatment were excluded from this study. Eventually, a total of 19 and 21 subjects were included in case and control groups, respectively. Cases played I-BiT™ games, while controls had standard patch therapy and played with placebo I-BiT™ games, both for one month. All subjects were examined at baseline and after one-month therapy. BCVA improved significantly in both groups after one-month treatment (case: P = 0.003, control: P < 0.001), while in comparison with each other, there was not any difference between them (P = 0.52). Although stereopsis improved in the case (P < 0.001) and control (P < 0.001), there was no significant difference between them pre and post-therapy. Our children played games for about 6 h total during one month in both groups, and their compliance was 87.5% and 76% in cases and controls, respectively. Two children were excluded due to their lower compliance of playing I-BiT™ games (n = 38). I-BiT™ game and patching with placebo game had similar BCVA improvement in amblyopic children after one-month treatment. It is suggested to conduct further randomized clinical trials with a larger sample size and longer duration of study and assessment of its recurrence.